Breast-feeding duration for the prevention of excess body weight of mother–child pairs concurrently: a 2-year cohort study. Issue 14 (19th June 2017) - Mastroeni, Marco Fabio; Mastroeni, Silmara Salete de Barros Silva; Czarnobay, Sandra Ana; Ekwaru, John Paul; Loehr, Sarah A; Veugelers, Paul J
Abstract: Objective: To examine the association between breast-feeding duration and the risk of excess body weight (children >85th percentile, mothers BMI≥25·0 kg/m 2 ) concurrently in mother–child pairs two years after delivery. Design: Prospective cohort study in Joinville, Brazil. Multivariable logistic regression was used to examine the independent relationship between breast-feeding duration and risk of excess body weight. Setting: Brazilian public maternity hospital. Subjects: Three hundred and five mother–child pairs. Results: At 2-year follow-up, 23·6 % of mother–child pairs had excess body weight. Children breast-fed for <2 months were more likely to have excess body weight than children breast-fed for ≥6 months (OR=2·4; 95 % CI 1·1, 5·1). Breast-feeding for <2 months was also associated with a greater likelihood of maternal excess body weight compared with those who breast-fed for ≥6 months (OR=2·9; 95 % CI 1·1, 8·1). There was a progressive increase in the likelihood of mother–child pairs having excess body weight as breast-feeding duration decreased. In addition to breast-feeding duration, other independent determinants of excess body weight were pre-pregnancy weight, gestational weight gain and number of pregnancies in mothers, and birth weight in children. Conclusions: Breast-feeding for a longer duration has a parallel protective effect on the risk of excess body weight in mother–child pairs two years after birth. Since members of the same family could be influenced by the same risk factors, continued promotion and support of breast-feeding may help to attenuate the rising prevalence of overweight in mother–child pairs.